Pancasila as the Ideology of the State and Nation - Andika Fikri Wirasena; Faiza Ryszard Ardana; Niken Ayu Nurmawati; Riska Andi Fitriono (CV. Rayyan Dwi Bharata, 2022)
Ideology has a central position for every nation. This main position is because ideology functions as a direction or guideline for the nation to achieve its goals. Furthermore, another function possessed by ideology is as a tool to stem the occurrence of social conflicts in society so that every society can live in centrism and also have a high sense of solidarity. Another function of ideology is to be a unifying tool of a nation. Every nation, of course, has diversity both in tribes, languages, customs, cultures, and so on. Therefore, in this article, the author intends to explore the position of pancasila as the ideology of the Indonesian nation. The research method used in this article is to explore supporting concepts such as e-books, articles, and the internet. The purpose of this writing is to explore the concept of pancasila which is positioned as the ideology of the Indonesian nation. Ideology has a function to unite the diversity that exists in society so that a good national and state life can be formed.